The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1519-6984.246194
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant effects of desvenlafaxine on modulating brain monoamine and oxidative stress in mice

Abstract: Desvenlafaxine succinate (DVS) inhibits serotonin reuptake selectively and is approved for major depressive disorders. This research investigated influence of DVS on modulating brain monoamine and oxidative stress in mice. The antiepileptic potential of DVS (10, 20, or 30 mg/kg/i.p.) in pentylenetetrazole (PTZ; 85 mg/kg) with i.p. route of administration, strychnine (STR; 75 mg/kg) with i.p. route, pilocarpine (400 mg/kg) with s.c. route and maximal electroshock MES-induced convulsion in mouse models. The acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…In this investigation 80 mg/kg of pioglitazone was dissolved in 0.1% carboxymethyl cellulos (w/v) and given to the mice orally (Rajaba et al, 2014). To induce seizure, 400 mg/kg of pilocarpine (a single dose) was administered intraperitoneally (IP) (Figure 1) (Alharbi, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this investigation 80 mg/kg of pioglitazone was dissolved in 0.1% carboxymethyl cellulos (w/v) and given to the mice orally (Rajaba et al, 2014). To induce seizure, 400 mg/kg of pilocarpine (a single dose) was administered intraperitoneally (IP) (Figure 1) (Alharbi, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Seizures, Alzheimer's disease, stroke, and migraine are the most common neurological ailments related to epilepsy (Farrell et al, 2017;Azimi and Asgarpanah, 2021;Alharbi, 2021). According to research, seizures have been demonstrated to attack neurons by causing oxidative stress and generating free radicals (Patel, 2002(Patel, , 2004Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation